2007
DOI: 10.1158/0008-5472.can-06-4040
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Features of Hormone-Refractory Prostate Cancer Cells by Genome-Wide Gene Expression Profiles

Abstract: One of the most critical issues in prostate cancer clinic is emerging hormone-refractory prostate cancers (HRPCs) and their management. Prostate cancer is usually androgen dependent and responds well to androgen ablation therapy. However, at a certain stage, they eventually acquire androgenindependent and more aggressive phenotype and show poor response to any anticancer therapies. To characterize the molecular features of clinical HRPCs, we analyzed gene expression profiles of 25 clinical HRPCs and 10 hormone… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
127
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(139 citation statements)
references
References 36 publications
5
127
0
1
Order By: Relevance
“…Tamura et al concluded that expression of HLA-A is downregulated when PCa cells progress from hormone therapy sensitive to hormone resistant PCa. 42 Downregulation of HLA-A may not have occurred in our patients' samples yet, as most cancers are in an early stage when a radical prostatectomy is performed. prevents progression through mitosis if metaphase is not completed properly.…”
Section: 33mentioning
confidence: 84%
“…Tamura et al concluded that expression of HLA-A is downregulated when PCa cells progress from hormone therapy sensitive to hormone resistant PCa. 42 Downregulation of HLA-A may not have occurred in our patients' samples yet, as most cancers are in an early stage when a radical prostatectomy is performed. prevents progression through mitosis if metaphase is not completed properly.…”
Section: 33mentioning
confidence: 84%
“…These clusters include many other genes that have not been identified earlier as androgen-responsive genes, and that may play significant roles in prostate cancer biology. Indeed, genes not identified earlier showing strong androgen regulation included the genes for nuclear receptor NR4A1, the cytokine receptor CXCR4 and insulin-like growth factor-1, which have all been implicated in prostate cancer progression (Akashi et al, 2006;Cheng et al, 2006;Tamura et al, 2007). The cluster analysis also indicates that levels of gene regulation by E2 and MPA are similar to those of CPA and OHF, suggesting that E2 and MPA act as SARMs.…”
Section: Androgen-regulated Gene Expression In Lncap Cells S Ngan Et Almentioning
confidence: 90%
“…Similarly, expression of the CXCR4 chemokine receptor, which is believed to play a role in cell motility and metastasis, and which has been implicated in many cancer types (Busillo and Benovic, 2007), including prostate cancer, was stimulated 19-fold by R1881 at 24 h, and was stimulated 1.9-2.9-fold by DHT, CPA, OHF and MPA, but was not stimulated by E2. NR4A1 is an orphan nuclear receptor that regulates apoptosis in many cancer cell types (Ke et al, 2004;Chintharlapalli et al, 2005) and whose expression is downregulated in hormone-refractory prostate cancer (Tamura et al, 2007). NR4A1 expression was stimulated 12-fold by R1881, with 1.9-3-fold stimulation by CPA, OHF, E2 and MPA.…”
Section: Androgen-regulated Gene Expression In Lncap Cellsmentioning
confidence: 99%
“…Moreover, five genes belonging to MHC were strictly downregulated in this network (H2-Q10, HLA-A, HLA-C, HLA-F, and HLA-G). Tamura et al (2007) observed down-regulation of HLA-A antigen in microarray analysis of hormone-refractory prostate cancer. We report the down-regulation of four genes (H2-Q10, HLA-C, HLA-F, and HLA-G) here for the first time.…”
Section: Discussionmentioning
confidence: 92%